(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Potapova O. M. The tasks as a way of forming a critical thinking among the students of technical specialties of higher education institutions in the study of mathematical analysis. The article examines the ways and means of forming critical thinking in the scientific and methodological sources while studying mathematical disciplines. The ways of its development among the students of technical specialties of higher schools in the process of studying mathematical analysis are determined in the article. The author proves the essential feature of forming a critical thinking among the students at mathematical analysis classes to be the special types of the tasks being researched in the article.